Penegakan Hukum Terhadap Pelaku Tindak Pidana Perjudian Online - Manalu, Hendri Saputra (Mahesa Research Center, 2019)
Gambling via the internet (internet gambling) usually occurs because of placing bets on sports or casino activities via the internet. Online gambling perpetrators can be convicted based on Article 27 paragraph (2) jo. Article 45 paragraph (2) of Law Number 19 Year 2016 concerning Information and Electronic Transactions. Online games are actually the whole process both the stakes, the game and the collection of money through the internet. The practice of online gambling is done by doing transactions in the form of selling chips which are then offered and bought by other people or certain agents to be sold / transferred to other interested poker accounts. These pins and chips will be sold for a certain price in cash (cash) in cash (rupiah). Information and Electronic Transactions precisely in Article 27 paragraph (2) and for the regulation of criminal acts is regulated in Article 45 of the Information Act and the electronic transaction. Law enforcement by the judge against the perpetrators of online soccer gambling crime in Medan District Court decision No. 870 / Pid.B / 2018 / PN.Mdn is by applying criminal sanctions against the makers of gambling criminal acts. Juridical obstacle in proving the crime of gambling is the lack of countermeasures made by the law enforcement authorities themselves, the law enforcers still use the old regulations to condemn the crimes against the perpetrators of this online gambling, while there are special regulations that regulate the crime of online gambling.